Argonaute-1 binds transcriptional enhancers and controls constitutive and alternative splicing in human cells - Alló, Mariano (2014)
The roles of Argonaute proteins in cytoplasmic microRNA and RNAi pathways are well established. However, their implication in small RNA-mediated transcriptional gene silencing in the mammalian cell nucleus is less understood. We have recently shown that intronic siRNAs cause chromatin modifications that inhibit RNA polymerase II elongation and modulate alternative splicing in an Argonaute-1 (AGO1)-dependent manner. Here we used chromatin immunoprecipitation followed by deep sequencing (ChIP-seq) to investigate the genome-wide distribution of AGO1 nuclear targets. Unexpectedly, we found that about 80% of AGO1 clusters are associated with cell-type-specific transcriptional enhancers, most of them (73%) overlapping active enhancers. This association seems to be mediated by long, rather than short, enhancer RNAs and to be more prominent in intragenic, rather than intergenic, enhancers. Paradoxically, crossing ChIP-seq with RNA-seq data upon AGO1 depletion revealed that enhancer-bound AGO1 is not linked to the global regulation of gene transcription but to the control of constitutive and alternative splicing, which was confirmed by an individual gene analysis explaining how AGO1 controls inclusion levels of the cassette exon 107 in the SYNE2 gene.